2023
DOI: 10.1093/jopart/muad002
|View full text |Cite
|
Sign up to set email alerts
|

Provider Ownership and Indicators of Service Quality: Evidence from Swedish Residential Care Homes

Abstract: The provision of public services by for-profit and non-profit organizations is widespread in OECD countries, but the jury is still out on whether outsourcing has improved service quality. This article seeks to nuance existing debate by bringing to the fore variation in service quality between different types of non-public providers. Building on theories of dimensional publicness and incomplete contracts, we argue that different forms of non-public ownership are associated with varying intensity of incentives f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The volume of studies that assessed health outcomes (n=4 total, 3 harmful, and 1 beneficial), costs to patients or payers (n=2 harmful), and costs to operators (n=2 harmful) was too small for conclusive interpretation. However, the findings of the 14 studies addressing quality roughly mirrored the proportions in the full sample, with six studies finding harmful impacts,373848496164 one study finding beneficial impacts,47 six studies finding mixed impacts,224050565859 and one study finding neutral impacts 60. In total, 12 studies identified some sort of harmful impact of PE ownership on nursing homes, and seven studies identified beneficial impacts.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The volume of studies that assessed health outcomes (n=4 total, 3 harmful, and 1 beneficial), costs to patients or payers (n=2 harmful), and costs to operators (n=2 harmful) was too small for conclusive interpretation. However, the findings of the 14 studies addressing quality roughly mirrored the proportions in the full sample, with six studies finding harmful impacts,373848496164 one study finding beneficial impacts,47 six studies finding mixed impacts,224050565859 and one study finding neutral impacts 60. In total, 12 studies identified some sort of harmful impact of PE ownership on nursing homes, and seven studies identified beneficial impacts.…”
Section: Resultsmentioning
confidence: 88%
“…Among studies that showed harmful impacts on quality, Bos and colleague found that PE owned nursing homes had lower employee quality and client recommendation scores compared with other for profit nursing homes, although this study had a critical risk of bias 38. Broms and colleagues61 found lower staffing density, education, and client ratings at PE owned nursing homes compared with various non-profit and private controls, and Patwardhan and colleagues64 had similar findings, wherein PE owned nursing homes were less likely to meet regulatory quality requirements, although both studies also had a serious risk of bias. Harrington and colleagues49 found increased deficiencies and severe deficiencies among PE owned nursing homes, and Bruch and colleagues41 found that PE owned hospitals had lower patient experience scores compared with control hospitals, but both these studies had a serious risk of bias.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations